Assessing the applicability of Hofstede's cultural dimensions for Global 500 corporations' Facebook profiles and content. Issue 1 (6th February 2017) - Lo, Kevin D.; Waters, Richard D.; Christensen, Nicklas
Abstract : Purpose: The purpose of this paper is to examine how Hofstede's six cultural dimensions are reflected on the official corporate Facebook pages from 259 organizations on Fortune magazine's Global 500 list. This is the first attempt to create a conceptualization of Hofstede's dimensions for organizational social media use. Design/methodology/approach: To determine how Facebook is used by the Global 500 corporations, a content analysis was carried out based on the 2013 listing of the highest revenue corporations throughout the world. As a research method, content analysis allows researchers to examine the actual practices of communication by focusing on the information provided through textual and visual messages. Findings: The results paint a mixed picture indicating that the global nature of these corporations is echoed in a somewhat similar overall presence on Facebook; but when the individual elements (About Us, updates, and media) are examined, statistical differences emerge in relation to the reflection of the cultural dimensions. Originality/value: To the authors' knowledge, this is the first work to match Facebook behaviors with Hofstede's dimensions. This work needs to be replicated with other organizations to determine its staying power. In addition, future research might tap into agency and any consciousness on the part of social media managers in a specific direction. Depending on those findings, they might make important statements on the emergence of a global social media culture.